(untitled) (Studia i Materiały Informatyki Stosowanej, 2013)
This article deals with proposal of universal access system which would utilize the standard input-output ports ofmicrocontroller. The whole proposal is based upon the ATmega64 processor, which makes the access system universal and very flexible. The main problem of this proposal is the USB communication decoding and creation of custom USB driver for TouchaTag reader.